PERAN BAHASA INDONESIA DALAM PEMBELAJARAN TEMATIK TERPADU MELALUI PENDEKATAN SAINTIFIK - NFN Yusnawarni (Balai Bahasa Provinsi Riau, 2014)
To commemorate the 21st century, a new learning model was designed in 2013 curriculum, in which there is a shift from teachers give knowledge to students become student must actively seek out knowledge from a variety of learning resources. In this case, the teacher acts as facilitators. Thus, language is a very central role, because the language should be in front of all other subjects. Curriculum 2013 imposed a thematic integrated learning which is no longer based subjects. Various subjects for primary schools (such as: Religion, Civics, Indonesian, Mathematics, Science, Social Studies, and so on) are integrated into one book. The subject matter is not presented in textbook, but it presented in book thematics lesson, the themes are about nature, social life and culture. In this new curriculum, learning process is implemented by applying a scientific approach (observing, questioning, experimenting, associating, and networking) that includes three aspects such as attitudes, knowledge, and skills. So, how is the role of Indonesian in an integrated thematic learning by applying scientific approaches in primary schools in 2013 curriculum? By appying the method, the object of this paper is to gain preview about the role of Indonesian in 2013 curriculum that uses integrated thematic learning by scientific approach in primary schools. Untuk menyongsong abad ke-21, model pembelajaran baru dirancang dalam Kurikulum 2013, yang di dalamnya terdapat pergeseran dari siswa diberi tahu menjadi siswa harus aktif mencari tahu ilmu pengetahuan dari berbagai sumber belajar. Dalam hal ini, guru berperan sebagai fasilitator. Dengan demikian, peran bahasa menjadi sangat sentral, karena bahasa harus berada di depan semua mata pelajaran lain. Kurikulum 2013 memberlakukan pembelajaran tematik terpadu yang tidak lagi berbasis mata pelajaran. Berbagai mata pelajaran untuk sekolah dasar (seperti: Agama, PPKN, Bahasa Indonesia, Matematika, IPA, IPS, dan sebagainya) diintegrasi menjadi satu buku. Materi pelajaran tidak disajikan dalam buku mata pelajaran, tetapi dalam buku tema pelajaran, baik tema alam, sosial, maupun budaya. Proses pembelajaran dalam kurikulum baru ini diimplementasikan melalui pendekatan saintifik (mengamati, menanya, menalar, mencoba, dan mengomunikasikan) yang mencakup tiga aspek, yaitu sikap, pengetahuan, dan keterampilan. Lalu, bagaimana peran bahasa Indonesia dalam pembelajaran tematik terpadu melalui pendekatan saintifik di sekolah dasar pada Kurikulum 2013 ini? Melalui metode deskriptif, yang menjadi tujuan penulisan ini adalah mendapatkan gambaran mengenai peran bahasa Indonesia dalam Kurikulum 2013 yang menggunakan pembelajaran tematik terpadu melalui pendekatan saintifik di sekolah dasar.